(untitled) (International Journal of Psychosocial Rehabilitation, 2020)
Fulfillment of Accreditation standards and the implementation of sustainability is needed so that hospitals provide services according to quality standards and patient safety. Monitoring is needed from management so that employees are motivated to implement Accreditation standards and are committed to running Accreditation standards. This study aims to obtain empirical evidence of the effect of supervision and motivation on post-accreditation employee commitment with employee satisfaction as an intervening variable. The research method uses quantitative methods with the type of causality. Data collected through surveys. The study was conducted at hospitals in the health service industry. Unit of analysis is the individual manager of the hospital unit. The number of samples is 180. Data analysis using Structural Equation Model (SEM). The results showed there was an influence of supervision, work motivation and job satisfaction on post-accreditation employee commitment simultaneously. Post-meditation employee commitment is influenced by job satisfaction and work motivation. Work motivation influences job satisfaction, giving rise to post-accreditation employee commitment. Job satisfaction can be an intervening variable between work motivation and post-accreditation employee commitment. The findings of the study are post-accreditation employee commitment arising from work motivation so as to make employees satisfied at work. This fosters employees’ dedication, integrity and sense of belonging to the importance of implementing Accreditation standards.